GAMBARAN FUNGSI TIROID PADA BAYI BARU LAHIR DI RSI SITI RAHMAH PADANG TAHUN 2023 - Anggraini, Debie; Muhammad Fharel; Rhandyka Rafli (Nusantara Hasana Journal, 2025)
Thyroid disorders, including congenital hypothyroidism (HK), can have a serious impact on a baby's development if not detected early. The congenital hypothyroidism (SHK) screening program aims to detect HK early in newborns. In Indonesia, the SHK program began in 2008 and in West Sumatra since 2011. Iodine deficiency in some regions increases the risk of thyroid disorders. Padang City will start implementing this program in 2023 at Siti Rahmah Hospital. This study describes thyroid function in newborns in the SHK program at Siti Rahmah Padang Hospital in 2023. This study analyzes the thyroid function of newborns in the SHK program at Siti Rahmah Padang Hospital in 2023. The study used a cross-sectional design with secondary data through the total sampling technique. This study analyzed the frequency distribution of TSH levels, gender, weight, body length, head circumference, chest circumference, abdominal circumspect, and gestational age in newborns (BBL) in the SHK program at Siti Rahmah Padang Islamic Hospital 2023. The majority of respondents had normal status in a variety of parameters, with more babies born at full term. Most newborns have euthyroid TSH with normal physical development. Genetic factors, maternal nutrition, and prematurity affect the growth and development of the baby.